Analysis of Special Legal Protection for Children Who Are Victims of Pornographic Crimes - Itok Dwi Kurniawan (JURNAL ILMIAH RESEARCH STUDENT, 2024)
This research aims to determine the legal protection efforts specifically provided to children who are victims of pornography crimes. Indonesian positive law in Law Number 35 of 2014 concerning Child Protection has provided special forms of protection for children which are oriented towards realizing the best interests of the child. This article was written using normative legal research methods with a statutory approach. Collection of legal materials is carried out by literature study of primary legal materials and secondary legal materials. The results of this research are that a special form of protection for child victims of pornography crimes is to provide recovery, especially in psychological aspects based on restorative justice. The aim and purpose of this recovery is so that children can live their lives as before without the trauma and pressure of being victims of pornographic crimes.